Centroiding para sensor de frente de onda robusto a truncamento - Pires, Henrique Sarti (2024)
For this generation of giant telescopes and observatories, adaptive optics systems have become an essential component for astronomical scientific observation. Unlike space telescopes, ground-based observatories have their imaging of astronomical objects affected by atmospheric turbulence, causing a blurring effect on the image and reducing the optical system’s resolution. To address this issue, the development and implementation of effective centroid-finding algorithms become crucial. Traditionally, techniques such as calculating the center of gravity, using adaptive filters like the matched filter, and correlation-based methods have been employed for this purpose. However, due to the complexity introduced by the truncation phenomenon, these traditional approaches are proving less effective. The importance of this challenge is evident in the context of the future Extremely Large Telescope (E-ELT), where the size of its telescope will be subject to point truncation. Therefore, it is essential to address the challenges posed by atmospheric turbulence and centroid truncation. Hence, this work aims to present and develop a novel centroid search and localization method specifically designed to handle the complexities introduced by atmospheric turbulence and truncation. This new method seeks to enhance the precision and effectiveness of correcting astronomical images in terrestrial environments, thus contributing to ongoing advancements in astronomical observation.